Konseling Islam dengan Terapi Forgiveness untuk Mereduksi Trust Issue pada Seorang Anak Terhadap Orang Tua - Putri Arum Pengajeng; Komaruddin Komaruddin; Lena Marianti (Journal of Society Counseling, 2025)
This study discusses the Application of Islamic Counseling with Forgiveness Therapy to Reduce Trust Issues in a Child Towards Parents (Case Study of Adolescents in Tulus Ayu Village, East Oku Regency). The purpose of the study is to find out the condition of children's trust issues with parents before Islamic counseling with forgiveness therapy, to find out the process of implementing the implementation of Islamic counseling with forgiveness therapy in reducing children's trust issues with parents and to find out the results of the process of implementing the implementation of Islamic counseling with forgiveness therapy in reducing children's trust issues towards parents. The method used in the study is qualitative. Data collection techniques include observation, interviews, and documentation. The results of the study showed: 1) The description of the child's trust issue with parents before Islamic counseling with forgiveness therapy was carried out, namely in the client showed an attitude that was easier to feel suspicious and difficult to trust with others, the client always had negative/bad thoughts, The client feels sad and uncomfortable when others comment about his family, the client also feels betrayed often, making it easier for the client to feel jealous, making the client keep his distance and it is very difficult to forgive the person. 2) The process of applying Islamic counseling with forgiveness therapy in reducing children's trust issues with parents, namely, first, problem identification: The client admits that he does not trust his parents. Second, diagnosis: the thought of counseling with his parents in the past that burdened his mind made him feel uncomfortable and affected his behavior in the present. Third, forgiveness therapy targets the emotional, cognitive, and interpersonal aspects of the client. Fourth, treatment: the client expresses his feelings or the uncovering phase, the client dares to make a decision or decision phase, the counselor tries to take action or work phase, and the stage where the counselor does a deepening phase. Fifth, evaluation: changes in the client because the counselor has given the task to the counselor to start getting used to reading the Quran, as an achievement of a calmer heart. 3) The result after the application of Islamic counseling with forgiveness therapy in reducing children's trust issues with parents is that there are behavioral changes shown by the counselor before and after the implementation of counseling.